EFEKTIVITAS WOLBACHIA DALAM PENGENDALIAN DEMAM BERDARAH DENGUE - Patmawati, Dewi; suparni, suparni; Mahwati, Yeni (Jurnal Sehat Masada, 2025)
Background: Dengue fever (DHF) is one of the global health threats that needs serious attention, because this disease has a high morbidity and mortality rate and has the potential to cause extraordinary events (KLB). Dengue control activities that dengue control activities that are usually carried out are considered ineffective, especially there are negative impacts including the existence of resistance in vectors to insecticides. The use of Wolbachia bacteria is offered as an alternative that can be applied in dengue control especially to reduce the cases. Objective: To determine the effectiveness of Wolbachia in controlling dengue fever control of dengue hemorrhagic fever. Methods: This article used narrative literature review method using data and information from online search sites such as Google Scholar, Pubmed and Science Direct published between 2019-2023. Discussion: A total of 8 out of 11 articles reported a decrease in dengue cases in Wolbachia release sites ranging from 40% - 96%. Another 3 articles stated that Wolbachia influenced the ability of Aedes aegypti mosquitoes to transmit dengue virus. Conclusion: Wolbachia is effective for dengue hemorrhagic fever control.